UHPC-based precast large-cantilevered thin-walled bent caps: Design and experiments. (1st December 2022) - Ye, Meng; Li, Lifeng; Hu, Fangjian; Wang, Lianhua; Shao, Xudong
Highlights: The UHPC-based precast large-cantilevered thin-walled bent caps were proposed and designed. The structural performance of two large-scale (12.1 m long) UHPC-based bent caps was experimentally investigated. The calculation methods for predicting the cracking strength and ultimate capacity of UHPC-based bent caps were proposed. The design considerations for the UHPC-based bent caps were proposed. Abstract: This study aimed to develop a new type of precast bent cap by using ultrahigh-performance concrete (UHPC) with prestressed tendons. The UHPC-based bent cap was designed to be lightweight and to exhibit excellent crack control as well as flexural and shear resistance. To this end, two large-scale specimens were designed and tested to identify their crack patterns, failure modes, shear behavior, and flexural behavior. The experimental results indicate that the UHPC bent caps provide excellent cracking resistance and considerable load-carrying potential after cracking, and the flexural strength dominates the design. In addition, calculation methods for the cracking strength and ultimate capacity were investigated and discussed, which can predict the strength of the UHPC bent cap with acceptable accuracy. Moreover, alternative options were proposed from different perspectives considering the construction procedure, weight reduction, and structural performance. Finally, several design considerations, i.e., the optimization of the cross-section and reinforcements, were proposed for prestressed UHPC-based bent caps.